The Human Rights Covenants at 50 : their past, present, and future - Moeckli, Daniel; Keller, Helen, 1964-; Heri, Corina (Oxford : Oxford University Press, 2018)
Half a century ago, on 16 December 1966, the UN General Assembly adopted the International Covenant on Civil and Political Rights (ICCPR) and the International Covenant on Economic, Social and Cultural Rights (ICESCR). While the adoption of the two UN human rights covenants was celebrated all over the world, their 50th anniversary has received very little attention from the international community. This text marks this anniversary by taking stock of the first half-century of the existence of what are probably the world's two most important human rights treaties. It does so by reflecting on what the covenants have achieved (or failed to achieve) in the years that have passed, by determining and comparing their current influence in the various regions of the world, and by assessing their potential roles in the future.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 13, 2018).
Keywords: International Covenant on Civil and Political Rights -- (1966 December 16); International Covenant on Economic, Social, and Cultural Rights -- (1966 December 16); Human rights; Law; International law